Gender affirmative care of transgender people: a single center's experience in Korea - Hyun Hye Lim; Yun Ha Jang; Gyu Yeon Choi; Jeong Jae Lee; Eun Sil Lee (Korean Society of Obstetrics and Gynecology, 2019)
ObjectiveTo investigate the clinical characteristics and medical management of transgender people in South Korea.MethodsThe electronic medical records of 54 transgender persons who had visited Soonchunhyang University Hospital from January 2016 to December 2017 for medical care were retrospectively reviewed. We identified patient demographics and gender identity-related characteristics. Moreover, we compared our hospital protocol with official guidelines.ResultsAt the time of the medical record search, the average age of these 52 transgender persons was 27 years, and 46 (88.5%) were Korean. Ten (19.2%) persons had a mental disorder other than gender dysphoria. Gonadotropin-releasing hormone agonist, estrogen, antiandrogen agents, and testosterone were used according to the guidelines issued by the World Professional Association for Transgender Health and the Endocrine Society. Ten (19.2%) transgender persons, including 6 (22.2%) male-to-females (MTFs) and 4 (16.0%) female-to-males (FTMs), had a mental disorder other than gender dysphoria. Among persons who were administered testosterone, 3 had high triglyceride and lipoprotein cholesterol levels. Nine patients, including 6 (66.7%) MTFs and 3 (33.3%) FTMs, underwent both gonadectomy and gender affirmative surgery. Seven (43.8%) persons, including 1 (14.3%) MTF and 6 (85.7%) FTMs, underwent only gonadectomy. There was a significant difference (P=0.040) between MTFs and FTMs.ConclusionMedical providers should have adequate knowledge of and experience in managing transgender persons and be familiar with the relevant guidelines and literature. Long-term follow-up examinations should also be performed.